2011
DOI: 10.1371/journal.pone.0023094
|View full text |Cite
|
Sign up to set email alerts
|

Increased Muscle Stress-Sensitivity Induced by Selenoprotein N Inactivation in Mouse: A Mammalian Model for SEPN1-Related Myopathy

Abstract: Selenium is an essential trace element and selenoprotein N (SelN) was the first selenium-containing protein shown to be directly involved in human inherited diseases. Mutations in the SEPN1 gene, encoding SelN, cause a group of muscular disorders characterized by predominant affection of axial muscles. SelN has been shown to participate in calcium and redox homeostasis, but its pathophysiological role in skeletal muscle remains largely unknown. To address SelN function in vivo, we generated a Sepn1-null mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 46 publications
3
61
1
Order By: Relevance
“…Recent studies using a zebrafish animal model revealed that SelN is required for early muscle development and differentiation in this organism (77,165). More recently, SelN Ϫ/Ϫ mice were developed (50,293). However, in contrast to what was observed in zebrafish, no abnormalities were found in the structure and the size of muscle fibers in SelN knockout mice.…”
Section: K Selenoprotein Nmentioning
confidence: 98%
“…Recent studies using a zebrafish animal model revealed that SelN is required for early muscle development and differentiation in this organism (77,165). More recently, SelN Ϫ/Ϫ mice were developed (50,293). However, in contrast to what was observed in zebrafish, no abnormalities were found in the structure and the size of muscle fibers in SelN knockout mice.…”
Section: K Selenoprotein Nmentioning
confidence: 98%
“…Loss of SEPN1 function is associated with increased oxidative stress in muscle [103], accelerated muscle pathology in the setting of physiologic stressors [104], and with abnormalities in muscle stem cells [105].…”
Section: Sepn1-related Myopathiesmentioning
confidence: 99%
“…These include reports on mice lacking functional genes for SelK [26], GPx2 [102], GPx3 [103], SelN [104], and SelR [105]. We are currently not aware of any publications on constitutive knockout mice for genes encoding Txnrd3, SelH, SelI, SelO, SelS, SelT, SelV, SelW, or SPS2.…”
Section: Constitutive Knockout Mice Studiesmentioning
confidence: 99%